Análisis cuantitativo de cuarzo-alfa en mezclas de cemento portland anhidro y calcita sintética por difracción de rayos X con equipo Philips PW-1700 - J. L. Sagrera-Moreno (Materiales de Construccion, 1985)
In this article there are explained the necessary steps to make up a quantitative analysis of alpha-quartz applying the technique of rays X diffraction, in artificial mixtures of anhydrous portland cement and synthetic calcite, which contents are known.